FACTORS AFFECTING PRICE EARNING RATIO AS ONE OF THE DECISION CRITERIA FOR MANUFACTURING COMPANY SHARES INVESTMENT IN INDONESIA STOCK EXCHANGE (2013-2018 PERIOD) - Safitri, Nurul Indah; Wiyono, Gendro (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims so that determine how the factors that affect the price earning ratio as one of the criteria for stock investment decisions of manufacturing companies on the Indonesia Stock Exchange for the period 2013-2018. Indicators of company characteristics used include the Dividend Payout Ratio, Debt to Equity Ratio, and Return on Assets to Price Earning Ratio. Dividend policy is based on the Dividend Payout Ratio, Debt to Equity Ratio, profitability is proxied by Return on Assets, and Company Value is prioritized by Price Earning Ratio. This study uses secondary data from financial reports and annual reports of companies included in manufacturing companies during 2013-2018. The research sample was determined using purposive sampling method, so that the sample obtained was about 8 companies. The results of hypothesis testing for each independent variable have a positive and significant effect on the dependent variable. Keywords : Dividend Payout Ratio, Debt to Equity Ratio, and Return on Assets and Price Earning Ratio